Recurrent Pericarditis, an Unexpected Effect of Adjuvant Interferon Chemotherapy for Malignant Melanoma - Farhan Ashraf; Fady Marmoush; Muhammad Ismail Shafi; Ashish Shah (Case Reports in Cardiology)
Drug-induced pericarditis is a well-described cardiac pathology that can result from a variety of medications; however, interferon-mediated pericarditis is extremely rare. We present a case of a young female with recurrent pericarditis due to interferon therapy. The role of interferon in adjuvant chemotherapy is well known and yields good effect, but this case highlights the very uncommon phenomena of interferon induced pericarditis and the significant distress it can cause.